IMPLEMENTATION OF PREVENTION PROGRAM FOR HEPATITIS B TRANSMISSION FROM MOTHER TO CHILD IN PUBLIC HEALTH CENTER OF SURABAYA - Manika Putri Kunigara; Bagus Setyoboedi; Sulistiawati Sulistiawati (Universitas Airlangga, 2022)
Introduction: The number of women with Hepatitis B in Surabaya has increased since 2015; the most significant increase occurred in Public Health Center (PHC) A and a consistently high at PHC B. The state has issued a guideline for preventing vertical hepatitis B transmission from mother to child through the Indonesian Ministry of Health issued the Minister of Health Regulation No. 52 of 2017. This program was in the open-access stage and focused on first-level health facilities in 2018-2019. Methods: For this reason, this study aims to analyze the implementation of the prevention program for Hepatitis B transmission from mother to child in PHC A and B, Surabaya, in 2019. This research was an exploratory, descriptive study with a qualitative approach through in-depth interviews and document review. Result: The study results indicated the lack of specificity of counseling materials and gaps in recording forms at PHC A. The presence of hepatitis B cadres as a promotion strategy at PHC B, incompleteness of filling out forms, achieving early detection coverage, not optimal pre- and post-early detection counseling activities, and coverage of case management were still below the target at both PHCs. Conclusion: the implementation of the prevention program for Hepatitis B transmission from mother to child is still not optimal, especially in health promotion at PHC A, surveillance, and case management at both PHC. Keywords: Implementation, Prevention, Transmission of Hepatitis B